PENGARUH GLASS CEILING TERHADAP PENGEMBANGAN KARIR WANITA DI DUNIA PENDIDIKAN - Tessa Shasrini; Al Sukri (Jurnal Ranah Komunikasi, 2021)
This research was conducted with a focus on the problem of Women's Career Development Glass. The total study is a conceptual framework structure built using quantitative research methods. Research is carried out with the aim of getting a goal. Namely “To Know the Effect of Glass Ceiling on Teacher-focused Women's Career Development. "At the same time, a hypothesis was developed to find out whether individual factors, family factors, organizational and cultural factors significantly influence Women's Career Development Factors. Only this study has been completed with a comprehensive empirical survey using a self-administered questionnaire and the sample consists of. of 110 female teachers. To present and analyze both descriptive and statistical data used. The findings reveal the Glass Ceiling and career development of women have a positive relationship, and also show that individual factors, organizational factors and cultural factors have a significant effect on development. Career of Women Whereas Family Factors have no effect on the Glass Ceiling The results of this study confirm that there is no effect on the effect of the glass ceiling. Taking all these facts into account, there is a better recommendation to be made in this study. In the end, the most important suggestion. Requirements for future research and study limitations have been outlined in this study.